2021
DOI: 10.1111/mpp.13147
|View full text |Cite
|
Sign up to set email alerts
|

Expression of putative effectors of different Xylella fastidiosa strains triggers cell death‐like responses in various Nicotiana model plants

Abstract: Plants respond to invading pathogens by exploiting their innate immune system. Microbe-associated molecular pattern (MAMP)triggered immunity (MTI) and effector-triggered immunity (ETI) have been described as the two main layers of defence during the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Interestingly EB92-1, a proposed X. fastidiosa biocontrol strain, lacks both Zot homologous genes found in Temecula1 strain (PD0915 and PD0928) [ 117 ]. Moreover, a X. fastidiosa Zot protein was shown to elicit cell death-like responses in the apoplast of some Nicotiana tabacum cultivars [ 34 ]. Besides Zot, other prophage-encoded genes may play a role in the biology of X. fastidiosa as observed in other bacteria, where the so called “moron” loci have been related to virulence, stress resistance, phage resistance and host adaptation [ 118 , 119 , 120 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly EB92-1, a proposed X. fastidiosa biocontrol strain, lacks both Zot homologous genes found in Temecula1 strain (PD0915 and PD0928) [ 117 ]. Moreover, a X. fastidiosa Zot protein was shown to elicit cell death-like responses in the apoplast of some Nicotiana tabacum cultivars [ 34 ]. Besides Zot, other prophage-encoded genes may play a role in the biology of X. fastidiosa as observed in other bacteria, where the so called “moron” loci have been related to virulence, stress resistance, phage resistance and host adaptation [ 118 , 119 , 120 ].…”
Section: Discussionmentioning
confidence: 99%
“…X. fastidiosa lacks the Type III secretion system (T3SS) [ 31 ], a membrane-embedded nanomachine typical of Gram-negative pathogens, which delivers effector proteins directly into host cells triggering or suppressing defense mechanisms, respectively in resistant or susceptible plants [ 32 ]. Instead, X. fastidiosa type II secretion system (T2SS) seems to be a relevant delivery apparatus of its virulence proteins [ 10 , 15 , 33 , 34 ]. It has been suggested that compatibility between xylem pit membrane carbohydrate composition and X. fastidiosa T2SS-secreted cell wall degrading enzymes is necessary for disease progression [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many pathogens use protein effectors, which reveal a variety of functions. These effectors are injected into the host cells helping pathogens to bypass host defense mechanisms (Büttner and Bonas, 2003; Kotsaridis, Tsakiri and Sarris, 2022; Sertedakis et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, host can recognize the pathogen effectors via specialized immunity receptors known as nucleotide binding leucine-rich repeat receptors (NB-LRR or NLR), which triggers the effector-triggered immunity (ETI) (Marchal et al ., 2022; Mermigka and Sarris, 2019; Jones and Dangl, 2006). This two-layered system leads to a variety of responses, such as accumulation of oxygen species, callose deposition, mitogen activated protein kinase activation and pathogenesis related gene expression (Sertedakis et al ., 2022; Yuan et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of WAK signalling improves anti‐bacterial immunity (Li et al ., 2020), but whether members of the WAK family and other RLKs are involved in cell wall integrity sensing on X. fastidiosa infection remains to be investigated. WAK receptors are also implicated in the immune response to LipA, a predicted lipase with homologues in X. fastidiosa that triggers cell death when expressed in the apoplast of tobacco species (Malukani et al ., 2020; Sertedakis et al ., 2022). Apoplastic expression of cell‐wall‐degrading enzymes and serine proteases induced cell death in tobacco species, suggesting recognition by PRRs that respond to apoplastic effector molecules (Sertedakis et al ., 2022).…”
Section: Xylella Fastidiosa and Interactions With The Plant Immune Sy...mentioning
confidence: 99%